Ccl2/Ccr2 signalling recruits a distinct fetal microchimeric population that rescues delayed maternal wound healing - Mathieu Castela (Nature Portfolio, 2017)
Foetal microchimeric cells (FMCs) are found in maternal circulation during pregnancy and migrate to injury sites, where they mediate repair, but how this is regulated is unclear. Here, the authors show in mice that the chemokine Ccl2 enhances delayed maternal wound healing through a subpopulation of Ccr2+ FMCs.